Supporting Complex Search Tasks - Awadallah, Ahmed; White, Ryen W.; Pantel, Patrick; Dumais, Susan; Wang, Yi-Min (The 23rd ACM Conference on Information and Knowledge Management (CIKM 2014), 2014)
We present methods to automatically identify and recommend subtasks to help people explore and accomplish complex search tasks. Although Web searchers often exhibit directed search behaviors such as navigating to a particular Website or locating a particular item of information, many search scenarios involve more complex tasks such as learning about a new topic or planning a vacation. These tasks often involve multiple search queries and can span multiple sessions. Current search systems do not provide adequate support for tackling these tasks. Instead, they place most of the burden on the searcher for discovering which aspects of the task they should explore. Particularly challenging is the case when a searcher lacks the task knowledge necessary to decide which step to tackle next. In this paper, we propose methods to automatically mine search logs for tasks and build an association graph connecting multiple tasks together. We then leverage the task graph to assist new searchers in exploring new search topics or tackling multi-step search tasks. We demonstrate through experiments with human participants that we can discover related and interesting tasks to assist with complex search scenarios.